Anti-microbial and anti-mycotoxigenic activities of endophytic Alternaria alternata isolated from Catharanthus roseus (L.) G. Don.: molecular characterisation and bioactive compound isolation. Issue 1 (2nd January 2019) - Sudharshana, T. N.; Venkatesh, H. N.; Nayana, Borah; Manjunath, K.; Mohana, D. C.
ABSTRACT: The present study investigated the anti-microbial and anti-mycotoxigenic activities of the ethyl acetate extract (EA) and a bioactive compound obtained from an endophytic fungus Alternaria alternata isolated from Catharanthus roseus leaves. A. alternata was identified using PCR-based 5.8S rDNA sequencing. The EA and bioactive compound, p -Coumaric acid (PC), showed concentration-dependent broad-spectrum anti-microbial activity against the tested bacteria, yeast, and fungi with MICs ranging from 7.8 to 250 µg/mL. The in vitro production of aflatoxin B1 (AFB1 ) from Aspergillus flavus and fumonisin B1 (FB1 ) from Fusarium verticillioides was completely inhibited by EA and PC at 400 µg/mL. The synthesis of the membrane-bound ergosterol from A. flavus and F. verticillioides was strongly inhibited by PC at 200 µg/mL. The EA and PC were found to show significant anti-microbial and anti-mycotoxigenic activities, hence, they could be explored as protective agents for preventing microbial deterioration and mycotoxins accumulation in food and feedstuffs during pre- and post-harvest and storage.